Software Design for IoT-based Organic Waste Recycling Disposal System - Li, Kun (fi=Turun yliopisto|en=University of Turku|, 2017)
In China, people are increasingly concerned about the rational and effective handling of garbage, especially how to effectively recycle the organic waste. However, up to now, the disposal methods of organic waste in our country are still in the stage of burying or burning. Although there have been organic waste harmless treatment equipment in the market, they have not been widely used due to high power consumption, low efficiency, high maintenance costs, etc.. This is not only a waste of the applied favorable condition with organic waste treatment technology, but also the popularity of organic waste harmless recycling in China is still low. To solve the above problems, this thesis proposes a set of information management system based on Internet of things (IoT). On the basis of organic waste processing equipment, a series of information methods would be used to improve the problem of the not- widely-used existing equipment through modifying the processing equipment, designing and implementing the corresponding system and its hardware and software. Based on its own network information platform, this system has modified all garbage treatment equipment (added sensors), and added all the modified processing equipment to the network information management platform in the form of node. Users no longer have to go on-site inspection of equipment for its maintenance and other reasons in space, because they can control or monitor remotely the equipment in real-time in the office. Thus, it not only reduces the number of required maintenance equipment, but also lowers the workload of the user. The system also has the corresponding information design function from the user information management and the equipment information management, and the device function to view the geographic location from the map; at the same time, in order to prevent users without the timely processing of fault from not checking the client device, the system has designed the function of SMS alerts. As long as the operation parameters of equipment are abnormal, the system will remind users in the form of text messages to improve the speed of the user to its equipment in a timely manner. In this thesis, we design and implement the software part of the system, including the client, server and database, as well as the hardware part, such as choosing and implementing sensor and communication module.